The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Manufacturing Engineering and Materials Handling, Parts a and B 2005
DOI: 10.1115/imece2005-79259
|View full text |Cite
|
Sign up to set email alerts
|

Issues Associated With MQL Implementation: Effect on Peripheral Milling Process Performance and Impact on Machining Economics

Abstract: The copious use of metal working fluids in machining applications carries with it worker health, environmental, and cost concerns. Driven by these concerns, minimum quantity lubrication (MQL) technology has been proposed as an intermediate alternative between flood and dry machining applications. However, widespread use of MQL is inhibited by worries related to unknown costs, thermal distortions, chip flushing problems, flammability of airborne metal dust, and system reliability/repeatability. More information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Few studies have performed an economic analysis of MQL versus conventional cooling in milling operations. Ju et al (2005) performed a cost analysis for a machining center and a transfer line for MQL and traditional cooling drilling, boring, and face filling operations.…”
Section: Fig 1 Different Cooling Methods In Metal Cuttingmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have performed an economic analysis of MQL versus conventional cooling in milling operations. Ju et al (2005) performed a cost analysis for a machining center and a transfer line for MQL and traditional cooling drilling, boring, and face filling operations.…”
Section: Fig 1 Different Cooling Methods In Metal Cuttingmentioning
confidence: 99%
“…The cost of flooded coolant was significantly higher than that of the MQL. The cost of flooded coolant was 22% higher than that of MQL (Ju et al, 2005). Amrita et al compared the costs of two systems that used low-and high-pressure compressed air with nanocutting fluid at 5 mL/min and 1 mL/min, respectively.…”
Section: Fig 2 Cost Distribution In Metal Cuttingmentioning
confidence: 99%
“…Peripheral milling tests were recently performed to examine the effects of fluid application strategy (dry, MQL, and fluid flood), axial depth of cut, flow rate, and air pressure. 38 The work concluded that while MQL application was not as successful as flood application in reducing the workpiece temperature, it did provide a sizeable improvement over dry machining. Increases in fluid flow rate and air pressure were found to reduce temperature and improve surface finish.…”
Section: Minimum Quantity Lubricationmentioning
confidence: 99%
“…Reduction in cutting temperature under the application of MQL attributed to increasing fluid flow rate and air pressure; was observed by Juet. al, 2005 [14]. Attanasioet.…”
Section: Introductionmentioning
confidence: 98%